#### Answer

$-4$
$-2$
$2$

#### Work Step by Step

$F(x)=(x-1)^2+1=x^2-2x+2$, therefore $F'(x)=2x-2+0=2x-2$
Therefore:
$F'(-1)=2\times(-1)-2=-4$.
$F'(0)=2\times(0)-2=-2$
$F'(2)=2\times(2)-2=2$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$-4$
$-2$
$2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.